PENGARUH PENERAPAN ELECTRONIC GOVERNMENT TERHADAP KUALITAS PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN KERINCI: ELIYUSNADI, S.Kom., M.Si - Eliyusnadi (JURNAL ADMINISTRASI NUSANTARA, 2019)
"This study aims to determine the effect of the application of electronic government on the quality of Dinas Kependudukan dan Catatan Sipil Kabupaten Kerinci. The formulation of the problem proposed is: Is there an Effect of the Application of Electronic Government on the Quality of Public Services in the Kerinci Regency Population and Civil Registry Office? How big is the effect of the application of electronic government on the quality of public services ?. Where the research results are based on the analysis of the independent variable Application of Electronic Government to the Quality of Public Services, where the value of t arithmetic is 0.960 with a significance level of 0.344> 0.05% or t arithmetic 0.960 <t table 2.733, then Ho is rejected Ha is accepted which means the Application of Electronic Government has no significant effect on the Quality of Public Services. Furthermore, based on the coefficient table it is known that the influence of Electronic Government on Service Quality is 0.085. Based on the analysis of the Electronic Government independent variable above it is known that the R Square value of 0.085 which means that the influence between Electronic Government, Against Quality of Service is 8.5%.